Clinical Presentation, Complications and Outcome of Measles in Pediatric Population at Tertiary Care Hospital: Measles in Pediatric Population - Kulsoom, Shazia; Soomro, Shazia; Junejo, Sadaf; Anjum, Misbah; Waseem, Hira; Akram, Marium (Pakistan Journal of Health Sciences, 2023)
Measles is highly contagious infection with person-to-person transmission through droplet infection in developing countries, which can lead to death in complicated cases. Bronchopneumonia, encephalitis, gastroenteritis with renal failure and electrolyte imbalance are common complications in pediatric age group. Objective: To determine complications of measles in hospitalized children at Tertiary Care Children Hospital. Methods: This cross-sectional study conducted at inpatient medical wards of National Institute of Child Health from July-Dec 2022. All patients hospitalized in study duration with the diagnosis of measles from 6 months till 12 years of age were enrolled. History, examination, laboratory tests, treatment and outcome were recorded and analyzed. Results: Children enrolled were 185, the mean age ± SD of presentation was 26.7 ± 27.1 months, with 56.8% males. Mean weight of patients was 10.48 ± 9.7kg. Common measles complications were bronchopneumonia 160(86.5%), acute diarrhea 64(34.6%) encephalitis 24(13%), myocarditis 16(8.6%), acute kidney injury 11(5.9%), and otitis media 18(9.7%). Conclusions: Most common clinical features were fever, maculopapular rash, cough and coryza. Bronchopneumonia was the main reason of hospitalization in majority of patients and leading cause of death in 13.5% of patients along with encephalitis and myocarditis. Additional strategies are required by government for elimination of vaccine preventable measles from Pakistan.